الأدوات الرابطة فى المقرر العربي فى المدارس الثانوية الماليزية : دراسة وصفية وتحليلية /‏ - Mohd Azizul Rahman Zabidin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This research studies the concept of al adawat al rabitah (cohesion by conjunction) in modem standard Arabic. It focuses on huruf al-'atf (conjunctions) and al 'ibarat al rabitah (conjunctive phrases) used in the construction of Arabic sentences. It aims to explore the aforementioned topic, which has become the syllabus in Malaysian Secondary Schools for those students who learn Arabic Language. In addition, the research also aims to understand the contents and analyse the credibility of teaching topics related to al adawat al rabitah to non-native of Arabic students. The research is carried out by employing descriptive analysis. The scope of analysis is given to the meanings, functions, and various usages of al adawat al rabitah in Arabic phrases. It also studies the usage of al adawat al rabitah in the syllabus, with the repetition of al adawat through statistical analysis. After the statistical part was conducted, the researcher made an analysis which was designed to give detailed overview of the contents of the textbook. The research had rendered several results and the researcher found that it is important for Secondary school students to master the usage of al adawat al rabitah in order to write mistake-free Arabic sentences. Secondly, the most frequently used al adawat al rabitah in the syllabus was 'Waw'. Thirdly, while the syllabus is designed to teach students al adawat al rabitah in Arabic phrases that have symbolical functions and meanings, it also presents to students the definition of al adawat al rabitah that is employed in every sentence, followed by Arabic texts containing those al adawat. Sometimes al adawat in Arabic are translated into Malay Language coupled with examples, explanations, and illustrations. Topic-related exercises follow each chapter and they vary according to specific topics. The research concludes with some recommendations for future teachers with regard to the teaching of adawat al rabitah in Secondary Schools in Malaysia.